P-124 UMBILICAL HERNIAS IN ADULTS: WHICH PROCEDURE? A RETROSPECTIVE STUDY OF OUTCOMES. (13th October 2022) - Oprea, V; Buia, F; Toma, M; Bucuri, C; Pavel, P; Grad, O
Abstract: Goal: To evaluate the outcomes of three procedures for adult umbilical hernias larger than 2.5 cm. Patients and methods: all adult patients with umbilical hernias larger than 2.5 cm admitted between 01 January 2018 and 30 December 2019 were included in the study. According to the surgeon's preference, three mesh procedures were performed: open Rives-Stoppa (o-RS), IPOM (with composite polypropylene mesh with polypropylene transparent film), and endoscopic Rives-Stoppa (e-RS). Demographics were included. The evaluated outcomes were duration of surgery, postoperative pain (on the VAS scale), local complications (seroma, hematoma, infections), and recurrence. Results: 57 patients fulfilled inclusion criteria and were distributed according to the operative procedure as follows: 28 patients with o-RS, 18 with IPOM, and 11 with e-RS. The mean age was 39.3 ± 8.2 years. Operative time was significantly shorter for o-RS patients compared with the other procedures (28.2 ± 12.7 min versus 41.7 ± 18.3 min for IPOM versus 124.3 ± 43.1 min for e-RS). No infection rate was reported. Equal rates of wound events were described. The pain was slightly increased in o-RS patients but only for the first 24 hours (4.1 ± 0.8) compared to 3.1 ± 0.2 for IPOM and 2.8 ± 0.5 for e-RS. An early recurrence rate was detected for each group of patients. Conclusions: According to our data o-RS, repair for umbilical hernia in adults is a valid and un-expensive procedure with similar immediate outcomes in terms of pain and wound events.